Guide for design and construction of pile foundations in permafrost - National Research Council of Canada. Division of Building Research (National Research Council of Canada, 1968)
Standards for the design and construction of pile foundations in permafrost represent an expansion of SNiP 11- A, 10-62 and 11-B, 5-62, and engineering specifications for the design of foundations in permafrost (SN 91-60), based on the experience in design and installation of pile foundations in Noril'sk, Yakutsk and other regions, and research data from various organizations. In these standards, recommendations are given for surveys, design, construction, inspection and testing of piles. The standards were developed in Krasnoyarsk by the Construction Research Institute, attached to the State Committee of the Council of Ministers (R.S.F.S.R.) for Building Problems. Les normes de conception et de construction des fondations sur pieux représentent une extension des normes SNiP 11-A, 10-62 et 11-B, 5-62 et des prescriptions techniques destiné es à la conception des fondations dans les zones de pergé lisol (SN 91-60). Ces normes et prescriptions sont basées sur l'expérience de la conception et de l'installation des fondations sur pieux acquise dans les régions de Norilsk, Yakoutsk et dans d'autres parties de l'U.R.S.S., ainsi que sur les données provenant des recherches entreprises par diverses organisations. Ces normes comportent des recommandations concernant l'étude, la conception, la construction, l'inspection et l'essai des pieux. Elles ont é té élaborées à Krasnoiarsk par l'Institut de recherche sur la construction, rattaché au Comité d'état du Conseil des ministres de l'Union soviétique chargé des problèmes de construction. Peer reviewed: No NRC publication: Yes